The Effect of Strength Conditioning on the Playing Skills of Sepaktakraw Athletes Universitas Pahlawan Tuanku Tambusai - Jufrianis (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. The purpose of this study was to determine the extent of the effect of strength conditioning training on the playing skills of sepak takraw athletes at Pahlawan Tuanku Tambusai University. Materials and methods. The method used is path analysis research method to see the direct influence between variable X on variable Y with a population and sample of 25 people. The data in this study are the results of strength and physical fitness conditioning tests which were analyzed using test requirements path analysis techniques. Results. The results of the research that has been conducted on the strength and conditioning variables on the physical fitness level of the Sepak Takraw Athletes at the University of Pahlawan Tuanku Tambusai found a direct influence between strength and conditioning (X1) the playing skills of the Sepak Takraw Athletes at the University of Pahlawan Tuanku Tambusai of 0.721. This can be seen in the Coffesient Table which shows the value of sig. 0.000. It turns out that the value of sig. 0.000 is smaller than the probability value of 0.05 or a value of 0.05 > 0.000, so it can be concluded that strength and conditioning have a direct effect on the playing skills of Sepak Takraw Athletes at Hero University Tuanku Tambusai. Conclusions. The Conclusion From the test results show that physical strength is very influential on the skills of playing Sepak Takraw on the athletes of the Hero University Tuanku Tambusai.